Method for the evaluation of the Usability of the Electronic Voting Software - UsabVEP - Núñez Marinovich, Néstor (2019)
The evaluation of software usability have an important role in the development of computer systems, because it reveals design and interactivity problems. The electronic voting software proposes great usability challenges because it automates task such as: verification of the identity of the voter, voting, scrutiny, results reports, transmission and presentation of results. Considering the existence of usability methods that are focused on different specific areas or being some very general, the need arises to propose a method adapted to the electronic voting software that allows to detect deficiencies in usability. In this work a method was developed to evaluate the usability of the electronic voting system called UsabVEP, this was applied in the electoral process software of a district of Lima, the results were analyzed, the system was validated and improvements were proposed. The method proposes two phases: 1. Heuristic evaluation and 2. Evaluation with users. The results show that the method developed found 46% more usability problems compared to the method of Jakob Nielsen, taken as a reference, for the electronic voting software in Peru.